2003
DOI: 10.1161/01.atv.0000084825.88022.53
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Specific p53 Expression Plays a Crucial Role in Atherosclerosis Development and Plaque Remodeling

Abstract: Objective-We first showed that absence of p53 accelerates atherosclerosis development in apoE-deficient mice. In this study, we investigated how macrophage-specific loss of p53 function might modulate atherosclerosis development in LDL receptor-deficient mice, a model for familial hypercholesterolemia. Methods and Results-We transferred bone marrow cells isolated from p53ϩ/ϩ and p53 Ϫ/Ϫ mice to lethally irradiated LDL receptor Ϫ/Ϫ mice and evaluated the aortic atherosclerotic lesion areas in the recipients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 29 publications
0
84
3
Order By: Relevance
“…p53 Ϫ/Ϫ apoE Ϫ/Ϫ mice disclosed a significant increase in arterial cell proliferation with no significant changes in apoptosis. The main findings of this study have been extended by the demonstration that reconstitution of irradiated LDL receptor-null mice 8 or apoE*3-Leiden transgenic mice 9 with p53-null bone marrowderived cells also accelerates atherosclerosis. Likewise, p27 inactivation, either globally 10 or in bone marrow-derived cells, 11 increases arterial cell proliferation and accelerates arteriosclerosis in fat-fed apoE-null mice.…”
Section: Role Of Cell Cycle-regulatory Factors In Neointimal Thickenimentioning
confidence: 72%
See 1 more Smart Citation
“…p53 Ϫ/Ϫ apoE Ϫ/Ϫ mice disclosed a significant increase in arterial cell proliferation with no significant changes in apoptosis. The main findings of this study have been extended by the demonstration that reconstitution of irradiated LDL receptor-null mice 8 or apoE*3-Leiden transgenic mice 9 with p53-null bone marrowderived cells also accelerates atherosclerosis. Likewise, p27 inactivation, either globally 10 or in bone marrow-derived cells, 11 increases arterial cell proliferation and accelerates arteriosclerosis in fat-fed apoE-null mice.…”
Section: Role Of Cell Cycle-regulatory Factors In Neointimal Thickenimentioning
confidence: 72%
“…Thus, in contrast to the reported intensification of atherosclerosis achieved on p27 or p53 inactivation in different induced murine models, [7][8][9][10][11] Merched and Chan 12 convincingly establish that p21 ablation, either globally or selectively in hematopoietic precursors, reduces both spontaneous and diet-induced atherosclerosis in apoE-null mice examined at different ages and under different nutritional regimens. Because transplantation of p21-null bone marrow cells into irradiated apoE-null mice reproduced most of the protective effect of whole-body p21 inactivation, including a thicker and better-formed fibrous cap, it was concluded that the absence of p21 expression in the neointimal macrophages is important to the beneficial effect against atherosclerosis.…”
Section: Absence Of P21 Is Now Shown To Protect Against Atherosclerosmentioning
confidence: 94%
“…As an essential and most important molecule in cell cycle and apoptosis control, p53 also plays a critical role in atherosclerosis [53][54][55] . Several studies demonstrated that the development of atherosclerosis was accompanied with the inactivation of p53 [56][57][58] .…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 99%
“…73 In this mouse model for familial hypercholesterolemia, loss of p53 stimulated proliferation in macrophages and was associated with unstable lesions, increased necrosis and with reduced collagen deposition, all bad prognostic features. 74 Macrophage migration into the fatty core of the plaque plays an important role in the genesis of dangerous lesions.…”
Section: Non-neoplastic Diseasesmentioning
confidence: 99%